MASSIVE COPPER-ZINC SULPHIDE DEPOSITS IN THE URALS - Prokin V.A.; Buslaev F.P. (My University, 1999)
The Urals is one of the most important regions in the world for the occurrence of volcanogenic massive sulphide deposits. Here are found 90 deposits of this type: 32 of them are worked out already, 16 are being worked now, 42 are explored but are not yet being worked. Some of the sulphide deposits, such as Gaiskoye, Uchalinskoye and Degtyarskoye are very large: their individual tonnages exceed 100 million. The volcanogenic massive sulphide deposits are the main sources supplying the copper- and zinc-productive plants of the region. Three types of the economic massive sulphide deposits: Cyprus, Urals, and Baimak types, are distinguished in the region. The main weight of the sulphide deposits is located within Tagil and Magnitogorsk troughs, while several others are situated in the Urals–Tobol uplift.The copper-dominant deposits of Cyprus type are hosted by tholeiitic basalt, which occurs in the basal parts of the Paleozoic volcanic sequences. They were formed near zones of ocean floor spreading. The copper–zinc sulphide deposits of Urals type are widespread in the region, being hosted by bimodal rhyolite–basalt assemblages. Deposits of this type were generated within back-arc and intra-arc basins along the paleovolcanic belts. The zinc–copper–barite deposits of Baimak type are connected with andesite–dacite–granite volcanic–plutonic complexes, which formed under island-arc conditions.A geological–geochemical model has been developed for the formation of the sulphide deposits of Urals type. According to this model, the deposits were formed during two stages: the first one, sedimentary-exhalative, took place within submarine volcanic depressions and the second one, hydrothermal-metasomatic, manifested itself after the sulphides of the first stage formation had been overlain by tuffs and lavas. The physical–chemical parameters of the first stage of ore formation have been determined as: temperature 250–300°C, pressure 200–400 bar, pH=3–6, Eh=−100 mV. For the second stage these parameters were: T=70–390°C, P=630–710 bar, pH=7.0–9.8, Eh=from +200 to 365 mV. The zonations of the ore bodies and haloes of wall-rock alteration were formed under the influence of the temperature and acidity–alkalinity fields which existed in the hydrothermal-metasomatic stage. The zones of rich ores were formed at this stage, due to leaching of the more mobile elements (Cu, Zn, Cd, Au, Ag) from parts of the ore bodies and their deposition in other parts.On the basis of the estimation of the addition and/or loss of elements in different zones of wall-rock alteration and disseminated ore, it can be shown that some elements were extracted from the host rocks (Fe, Cu, Zn) while others were supplied by endogenous fluids (K, Si, S).Modification of sulphide ores took place in several sulphide deposits of the Urals. These stages are: (1) pyrrhotite (330–520°C); (2) bornite (190–270°C); (3) regional metamorphism under variable facies conditions; (4) contact metamorphism (500–620°C). Nevertheless, some of the deposits have a very well-preserved character, they non-deformed and non-metamorphosed. The Urals may serve as a standard for comparative studies of the volcanogenic massive sulphide deposits in other orogenic belts.
Keywords: Paleozoic; Paleozoic; Палеозой